2017
DOI: 10.3390/jof3040062
|View full text |Cite
|
Sign up to set email alerts
|

Ecoepidemiology of Cryptococcus gattii in Developing Countries

Abstract: Cryptococcosis is a systemic infection caused by species of the encapsulated yeast Cryptococcus. The disease may occur in immunocompromised and immunocompetent hosts and is acquired by the inhalation of infectious propagules present in the environment. Cryptococcus is distributed in a plethora of ecological niches, such as soil, pigeon droppings, and tree hollows, and each year new reservoirs are discovered, which helps researchers to better understand the epidemiology of the disease. In this review, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 115 publications
(169 reference statements)
3
25
0
1
Order By: Relevance
“…Clinical data from this study showed that almost all patients had no obvious immunodeficiency, except one patient with SLE, which was consistent with the fact that the C. gattii species complex causes infection in immunocompetent hosts [11]. Most strains in Guangxi, southern China had the capabilities to produce melanin and capsule, as well as to undergo sexual reproduction.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 83%
See 1 more Smart Citation
“…Clinical data from this study showed that almost all patients had no obvious immunodeficiency, except one patient with SLE, which was consistent with the fact that the C. gattii species complex causes infection in immunocompetent hosts [11]. Most strains in Guangxi, southern China had the capabilities to produce melanin and capsule, as well as to undergo sexual reproduction.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 83%
“…Cryptococcosis is a global and invasive systematic mycosis caused by C. gattii/neoformans species complexes, leading to morbidity and mortality in both immunocompetent and immunocompromised individuals, such as those with acquired immune deficiency syndrome (AIDS) or those undergoing organ transplantation [11]. Infections due to C. neoformans species complex occur worldwide while cryptococcosis caused by C. gattii species complex was traditionally considered an endemic disease, and associated with tropical and subtropical climates [11]. However, the outbreaks of C. deuterogattii in humans and a wide range of mammals in Vancouver Island and the PNW of the USA demonstrates that the fungus has adapted to environments beyond the endemic (sub)tropical regions [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In general, differences among them are noted for in vitro antifungal susceptibility. From the pre‐HIV era until the present, C. gattii has shown higher MICs to antifungals compared to C. neoformans 5,33,35,36,41 . C. deuterogattii clinical isolates follow this trend exhibiting higher MIC for fluconazole ( P = .0101) and itraconazole ( P = .0018) than C. neoformans clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Several yeast species have adaptations to face phagocytosis, as well as the ability to form biofilms together with bacteria (Modrzewska & Kurnatowski, ; Holland et al, ; Glöckner & Cornely, ; Priest & Lorenz, ). Cryptococcus is a yeast‐like member of the Tremellomycetes that causes pneumonia and meningitis (Chaturvedi & Chaturvedi, ; Kwon‐Chung et al, ; Srikanta, Santiago‐Tirado & Doering, ; Dylag, ; Herkert et al, ). The fungus presents a mutinucleated and highly polyploid titan cell that seems to avoid phagocytosis thanks to its sheer size, and from which apparently regular‐sized cells emerge and colonize.…”
Section: Fungi and Animalsmentioning
confidence: 99%